2012
DOI: 10.1111/j.1439-0396.2011.01270.x
|View full text |Cite
|
Sign up to set email alerts
|

Rumen microbial variation and nutrient utilisation in mithun (Bos frontalis) under different feeding regimes

Abstract: The aim of the study was to investigate the effect of feeding different diets on fermentation, enzyme activities and microbial population in the rumen fluid of mithun (Bos frontalis). In a randomized block design, 20 male mithun (6-8 months of age, 152 ± 12.6 kg body weight) were randomly divided into four experimental groups (n = 5/group) and fed experimental diets ad libitum for 180 days. The diet R1 contained tree foliages (TF), R2 comprised of 50% concentrate mixture (CM) and 50% TF, R3 contained 50% CM an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…We found here that the increase in ruminal ammonia N concentration was directly associated with the observed plasma urea concentration ( Figure 1 a). In agreement with our findings, Migliano et al [ 59 ] likewise reported a strong positive correlation between ruminal ammonia N and plasma urea N. The inclusion of improved forages in TMR diets might contribute to highly degradable protein sources that decreased ruminal ammonia N concentrations, but ruminal ammonia N likely remained adequate for microbial growth [ 60 ]. The ruminal pH that we obtained is normal for lactating dairy cows fed roughage-based diets [ 52 ], perhaps because the dietary NDF concentrations of all of the dietary treatments were sufficient to maintain the optimal ruminal pH for cows fed high-forage diets.…”
Section: Discussionsupporting
confidence: 92%
“…We found here that the increase in ruminal ammonia N concentration was directly associated with the observed plasma urea concentration ( Figure 1 a). In agreement with our findings, Migliano et al [ 59 ] likewise reported a strong positive correlation between ruminal ammonia N and plasma urea N. The inclusion of improved forages in TMR diets might contribute to highly degradable protein sources that decreased ruminal ammonia N concentrations, but ruminal ammonia N likely remained adequate for microbial growth [ 60 ]. The ruminal pH that we obtained is normal for lactating dairy cows fed roughage-based diets [ 52 ], perhaps because the dietary NDF concentrations of all of the dietary treatments were sufficient to maintain the optimal ruminal pH for cows fed high-forage diets.…”
Section: Discussionsupporting
confidence: 92%
“…Given that when grazing, Tibetan sheep ingest a high-variety diet, as they encounter different habitats and a variety of food types in the pasture, this can cause adaptive responses of the intestinal microbiota. As such, feeding strategy choice may provide a unique opportunity to manipulate the complex microbial ecosystem ( 22 ). Studies have demonstrated distinct rumen fermentation patterns of sheep switched from natural grazing to indoor feed depending on the feeding strategies (i.e., semigrazing with supplementation or barn feeding) ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, both of their vitalities were depressed in high-Mo group. Ammonia nitrogen concentration had a close relationship with bacteria, and more than 50 % dietary protein would be degraded into ammonia nitrogen by ruminal bacteria [25,26]. It was suggested that excessive Mo had profound effects on activity of microorganism samples, which disturbed absorption and utilization of nutrients [20].…”
Section: Discussionmentioning
confidence: 98%